2022
DOI: 10.3389/fmicb.2022.856454
|View full text |Cite
|
Sign up to set email alerts
|

Landscape Topography and Regional Drought Alters Dust Microbiomes in the Sierra Nevada of California

Abstract: Dust provides an ecologically significant input of nutrients, especially in slowly eroding ecosystems where chemical weathering intensity limits nutrient inputs from underlying bedrock. In addition to nutrient inputs, incoming dust is a vector for dispersing dust-associated microorganisms. While little is known about dust-microbial dispersal, dust deposits may have transformative effects on ecosystems far from where the dust was emitted. Using molecular analyses, we examined spatiotemporal variation in incomin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 113 publications
0
2
0
Order By: Relevance
“…Future research also needs to complement metagenomically identified bacteria and fungi by monitoring culturability to better assess microorganisms’ role in ecosystem, human, plant, and animal health. ,,,, Such studies should also measure other water-soluble aerosol components and metal speciation, some of which might affect viability. Additionally, airborne pollutants have the capacity to influence aerobiome abundance, diversity, transport, and deposition, and conversely, bioaerosols can facilitate the transport and deposition of airborne pollutants. , The interplay between bioaerosols and anthropogenic emissions is complex and dependent on multiple factors, including pollutant type, concentration levels, and meteorological parameters.…”
Section: Implications and Future Workmentioning
confidence: 99%
“…Future research also needs to complement metagenomically identified bacteria and fungi by monitoring culturability to better assess microorganisms’ role in ecosystem, human, plant, and animal health. ,,,, Such studies should also measure other water-soluble aerosol components and metal speciation, some of which might affect viability. Additionally, airborne pollutants have the capacity to influence aerobiome abundance, diversity, transport, and deposition, and conversely, bioaerosols can facilitate the transport and deposition of airborne pollutants. , The interplay between bioaerosols and anthropogenic emissions is complex and dependent on multiple factors, including pollutant type, concentration levels, and meteorological parameters.…”
Section: Implications and Future Workmentioning
confidence: 99%
“…At each of four sites, we collected dust using passive collectors; our collectors consisted of a modified round bundt pan (Nordic Ware, Minneapolis, MN, USA) coated with Teflon (25.4 cm in diameter), which was lined with Kevlar mesh (Industrial Netting, Maple Grove, MN, USA), as described in Aciego et al (2017) 24 and Maltz et al (2022). 25 Glass marbles were suspended from the bottom and rested atop the mesh within the pan. Pans were fitted with overarching cross-braced strapping, which was covered in bird repellent (Bird-X, Elmhurst, IL, USA) to deter bird visitation or roosting.…”
Section: Sample Collectionmentioning
confidence: 99%